Training on the Use of Management Information Systems for Improving the Quality of Service Document - Tarigan, Azhari Akmal; Syafira, Dinda; Padillah, Fahmil (Taqaddum: Community Service Journal, 2023)
The essence of government in an area is to provide assistance to the surrounding environment, basically public authority is "local regional assistance" the public authority has not been made for itself other than serving the surrounding environment. Due to advances in technology, information and correspondence, ideal opportunities in the creation of population records, the use of expert services in handling population reports, the high need for population records has become the cause of assessment problems. Therefore, the reason for conducting this study is to know and describe the development of the data collection framework for the aid implementers and the nature of the administration of population reports at the Medan City Population and Civil Registration Office, to find out the procedures carried out to achieve these goals. make it easier for the public in general to make population information. Therefore, specialists The essence of this logical work is to make use of an emotional procedure that uses the peculiarities that occur in the climate and the reality that arises by collecting data about an object of investigation. The results and discussion of this study are the use of document preparation services at the Medan City Population and Civil Registration Office. Executives' data is essential to ensure the perfection and timeliness spent in making population documents. Precise and complete data: The information expected to prepare the report should be collected carefully and clearly. By carrying out good data management, registration administration services at the Medan City Population and Civil Registration Office can run more productively and smoothly, so that it can provide better assistance to the local area.